Congenital anomalies in Ibadan, Nigeria (2016)
Background: There is a need for a multidisciplinary database that can be used as a potential source for developing a protocol and a guideline for a possible nationwide prospective surveillance of congenital anomalies in Nigeria. Methods: This five-year cross-sectional retrospective survey of data from January 2009 to December 2013 was done at the University College Hospital, Ibadan. Data were collected from the admission records on the wards in 8 specialty units with the most workable documented clinical records of congenital anomalies in their care using a predesigned proforma. Proportions of congenital anomalies were determined based on systemic classification of the anomalies and the descriptive terms used were according to the ICD_10-chapter XVIII_RCPCH extension. Result: The total number of patients with congenital anomalies whose records were obtained from the ward registers was 1311, there were 75 (5.7%) missing case notes while information was obtained on 1236 (94.3%) patients. There were a total of 1479 anomalies with multiple anomalies seen in 16.1% of the patients. The male/female ratio was 2:1 and multiple births as well as positive family history of birth defects were seen in about 2.4% and 2.2% of cases respectively. Prenatal diagnosis of the anomalies was documented in only 11 cases (0.9%). Only about one in five cases presented within the neonatal period, and defects of the abdominal wall as well as the cranial-facial-orbital regions were the most prevalent. Next were those in the cardiovascular, spinal column, anorectal and genital, as well as musculoskeletal systems. Conclusion: The size and pan-systemic profiles of the birth defects documented in this study calls for further action on this all-important cause of childhood mortality and significant life-long morbidity in our country.